Renal Sympathetic Denervation Attenuates Congestive Heart Failure in Angiotensin II-Dependent Hypertension: Studies with Ren-2 Transgenic Hypertensive Rats with Aortocaval Fistula - Honetschlagerová, Zuzana; Gawrys, Olga; Jíchová, Šárka; Škaroupková, Petra; Kikerlová, Soňa; Vaňourková, Zdeňka; Husková, Zuzana; Melenovský, Vojtěch; Kompanowska-Jezierska, Elzbieta; Sadowski, Janusz; Kolář, František; Novotný, Jiří; et al. (Kidney & blood pressure research, 2021)
OBJECTIVE: We examined if renal denervation (RDN) attenuates the progression of aortocaval fistula (ACF)-induced heart failure or improves renal hemodynamics in Ren-2 transgenic rats (TGR), a model of angiotensin II (ANG II)-dependent hypertension. METHODS: Bilateral RDN was performed 1 week after creation of ACF. The animals studied were ACF TGR and sham-operated controls, and both groups were subjected to RDN or sham denervation. In separate groups, renal artery blood flow (RBF) responses were determined to intrarenal ANG II (2 and 8 ng), norepinephrine (NE) (20 and 40 ng) and acetylcholine (Ach) (10 and 40 ng) 3 weeks after ACF creation. RESULTS: In nondenervated ACF TGR, the final survival rate was 10 versus 50% in RDN rats. RBF was significantly lower in ACF TGR than in sham-operated TGR (6.2 ± 0.3 vs. 9.7 ± 0.5 mL min-1 g-1, p < 0.05), the levels unaffected by RDN. Both doses of ANG II decreased RBF more in ACF TGR than in sham-operated TGR (-19 ± 3 vs. -9 ± 2% and -47 ± 3 vs. -22 ± 2%, p < 0.05 in both cases). RDN did not alter RBF responses to the lower dose, but increased it to the higher dose of ANG II in sham-operated as well as in ACF TGR. NE comparably decreased RBF in ACF TGR and sham-operated TGR, and RDN increased RBF responsiveness. Intrarenal Ach increased RBF significantly more in ACF TGR than in sham-operated TGR (29 ± 3 vs. 17 ± 3%, p < 0.05), the changes unaffected by RDN. ACF creation induced marked bilateral cardiac hypertrophy and lung congestion, both attenuated by RDN. In sham-operated but not in ACF TGR, RDN significantly decreased mean arterial pressure. CONCLUSION: The results show that RDN significantly improved survival rate in ACF TGR; however, this beneficial effect was not associated with improvement of reduced RBF or with attenuation of exaggerated renal vascular responsiveness to ANG II.
Keywords: Angiotensin II; potkani transgenní; angiotensin II; hypertenze; srdeční selhání; Renal vascular reactivity; potkani Sprague-Dawley; Renal denervation; Kidney; Hypertension; Rats, Transgenic; krysa rodu Rattus; arteriovenózní píštěl; Animals; Arteriovenous Fistula; Aortocaval fistula; ženské pohlaví; Renin; Heart Failure; ledviny; zvířata; Rats; sympatektomie; Renal blood flow; Female; Sympathectomy; Congestive heart failure; renin; Rats, Sprague-Dawley